2019 Novel Coronavirus Infection: Gastrointestinal Manifestations - Samanta, Jayanta; Dhar, Jahnvi; Khaliq, Abdul; Kochhar, Rakesh (Journal of Digestive Endoscopy, 2020)
The world is witnessing a major public health crisis in the wake of the third coronavirus strain pandemic, a novel coronavirus (severe acute respiratory syndrome coronavirus 2). Although initially thought to be a pure respiratory pathogen, recent reports have highlighted not only the extrapulmonary effects of the virus but also, importantly, the gastrointestinal tract (GIT) effects. Various studies have looked into the effects of this novel coronavirus infection (coronavirus-19 disease [COVID-19]) on GIT involvement with reports of more frequent involvement than previously expected. With feco-oral transmission, debate being conclusively proven with fecal samples testing positive for COVID-19 and longer shedding time, it only underlines the importance of GIT involvement. Moreover, the presence of other GI diseases, such as inflammatory bowel disease, with COVID-19 infection might wreak havoc leading to poor patient outcomes.
Keywords: SARS-CoV-2; COVID-19; gastrointestinal symptoms; coronavirus; fecal shedding; digestive symptoms; feco-oral transmission